Remote C–H Functionalization via Selective Hydrogen Atom Transfer - Stateman, Leah M.; Nakafuku, Kohki M.; Nagib, David A. (Synthesis, 2018)
The selective functionalization of remote C–H bonds via intramolecular hydrogen atom transfer (HAT) is transformative for organic synthesis. This radical-mediated strategy provides access to novel reactivity that is complementary to closed-shell pathways. As modern methods for mild generation of radicals are continually developed, inherent selectivity paradigms of HAT mechanisms offer unparalleled opportunities for developing new strategies for C–H functionalization. This review outlines the history, recent advances, and mechanistic underpinnings of intramolecular HAT as a guide to addressing ongoing challenges in this arena.1 Introduction2 Nitrogen-Centered Radicals2.1 sp3 N-Radical Initiation2.2 sp2 N-Radical Initiation3 Oxygen-Centered Radicals3.1 Carbonyl Diradical Initiation3.2 Alkoxy Radical Initiation3.3 Non-alkoxy Radical Initiation4 Carbon-Centered Radicals4.1 sp2 C-Radical Initiation4.2 sp3 C-Radical Initiation5 Conclusion
Keywords: hydrogen atom transfer; remote C–H functionalization; radicals; nitrogen-centered radicals; oxygen-centered radicals